Systematic observation of participatory interaction in university lectures: a multiple case study with a mixed methods approach - Tronchoni, Héctor; Izquierdo, Conrad; Anguera, M. Teresa (Frontiers in Psychology, 2024)
Introduction: The concern to improve and innovate the face-to-face instructional task in postgraduate and doctoral university teaching encompasses different formats of participatory interaction, considered as social medium facilitators of deep learning that includes the development of autonomous expert activity. The purpose of this article is to position the use of systematic observation and lag sequential analysis as a conceptual-methodological choice to base the review of social-constructivist instructional practice that is taught with an expository format prepared by the teacher. Method: The systematic observation of the expert's expository session from beginning to end was approached from a mixed methods perspective, as an object of multiple case study. Four postgraduate teachers were selected. A purpose-built observational instrument was constructed. The data quality was tested with intra-observer agreement tests by calculating Cohen's kappa coefficient (k). Once the data matrices for each case had been obtained, all possible file aggregations of the data were carried out to detect the existence of common structures in the patterns through lag sequential analysis. Results: The sequential patterns of replicated and common lags of the multiple case describe the chaining of the observed events that characterizes the participatory interaction. Twelve lag sequential patterns have been discovered that function as dialogical links generated by the probability that the category “question” is linked to the conditioned events: “speech direction” and “exchange orientation”. Discussion: Having constructed a theoretical interpretative scheme of the replicated patterns, we discuss the results: Firstly, the significant results of the lag sequential analysis as examples of basic patterns extracted from their way of conducting expert expository sessions; as such, they can be reviewed with the formative purpose of reflecting on their potential for change when they are understood as dialogical links of participatory interaction committed to deep learning and the development of expert autonomy. Secondly, a training step consisting of the use of self-observation and the observation that teachers can make of the expert expository task. Finally, we conclude that non-intrusive systematic observation is a good choice when channeling the gradual and renewed improvement of participatory interaction with an expert expository format and a mixed methods methodology.